Atención farmacéutica a paciente de 68 años con diagnóstico de diabetes mellitus tipo ii administrando insulina como tratamiento farmacológico electivo - Chamba Guadalima, Daniela Fernanda (Machala : Universidad Técnica de Machala, 2019)
Diabetes mellitus is a disease caused by obesity, sedentary lifestyle, family history of type 2 diabetes, people over 40 years of age, ingestion of saturated fat and hing blood pressure. The knowledge of risk factors will allow the development of preventive activities, promoters and health policies in the population and decrease the rates of the disease and its complications. The OMS in 2014 reveals 422 million people aged 20 to 79 years diagnosed with Diabetes Mellitus; it will be the seventh cause of mortality for 2030; in Ecuador; it constitutes the first cause of mortality with 7.44% and a mortality rate of 29.76. A descriptive and analytical method of study was applied. The main objective of this research is to develop a pharmaceutical care program through health education, pharmacotherapy monitoring, healthy lifestyle habits, to prevent or delay the appearance of complications associated with the disease. A pharmaceutical care program is proposed for the patient, the problems related to the medication are indentified, detecting that she received an incomplete pharmacotherapy (potential problem) and was administered hypoglycaemic medication without monthly control of the glycemia (real problem). Problems related to pharmacotherapy are prevented and solved, the administration of a medication without a valiadated indication or control examinations being of high priority. Sugar levels are stabilized, to solve problems related to medications and the prevention of complications derived from the disease such as ulcerations, diabetic foot, neuropathy, retinopathy and nephropathy.
La diabetes mellitus es una enfermedad provocada por obesidad, sedentarismo, antecedente familiar de diabetes tipo 2, personas mayores de 40 años, ingestión de grasa saturada e hipertensión arterial. El conocimiento de factores de riesgo permitirá desarrollar actividades preventivas, promotoras y políticas de salud en la población y disminuir las tasas de la enfermedad y de sus complicaciones. La OMS en el año 2014 revela 422 millones de personas de entre 20 a 79 años diagnosticadas con Diabetes Mellitus; será la séptima causa de mortalidad para el 2030; en el Ecuador, constituye la primera causa de mortalidad con el 7.44% y una tasa de mortalidad de 29.76. Se aplicó un método de estudio de tipo descriptivo y analítico .El objetivo principal de ésta investigación es elaborar un programa de atención farmacéutica mediante la educación sanitaria, seguimiento farmacoterapéutico, hábitos de vida saludable, para prevenir o retrasar la aparición de complicaciones asociadas a la enfermedad. Se propone un programa de atención farmacéutica para la paciente, se identifica los problemas relacionados con la medicación, detectando que recibía una farmacoterapia incompleta (problema potencial) y se le administró medicación hipoglucemiante sin control mensual de la glucemia (problema real). Se previene y resuelve problemas relacionados con la farmacoterapia, siendo de prioridad alta la administración de un medicamento sin una indicación validada ni exámenes de control. Se estabilizan los niveles de azúcar, para solucionar problemas relacionados con los medicamentos y la prevención de complicaciones derivadas de la enfermedad como las ulceraciones, pie diabético, neuropatía, retinopatía y nefropatía.
Keywords: POLIURIA; POLIDIPSIA; MACROANGIOPATICAS; NEUROPATIA